The Role of the Pusaka Raudhatul Irfan Islamic Boarding School in Cultivating Fair and Civilized Human Values Among Boarding School Students - Iskandar, Suhenda; Sanusi , Aris Riswandi; Susanto, Erwin (Journal of Educational Sciences, 2025)
This study aims to describe the role of the Pusaka Raudhatul Irfan Islamic Boarding School in shaping the habituation of fair and civilized human values in the lives of students. The background of this study is the concern over the erosion of Pancasila values amid the tide of modernization that influences the character of adolescents, such as the rise of individualism, intolerance, and low social awareness. The approach used is qualitative descriptive with techniques of observation, interviews, and documentation conducted from May to June 2025 in Karawang Regency. The results of the study indicate that the pesantren actively applies values of equality, respect for diversity, a spirit of mutual care, and freedom of expression in the daily lives of the students. This is manifested through communal living, mixing students from different regions, consultation forums, mentoring, and extracurricular activities. Despite challenges such as mild verbal discrimination and potential cultural conflicts, the boarding school successfully addresses these issues through a family-oriented approach and moral education. This entire process positions the boarding school as a strategic institution in character education rooted in the values of the second principle of Pancasila.